MUSIC THERAPY - AN INNOVATION: संगीत चिकित्सा - एक नवाचार - mehra, Lata (International Journal of Research -GRANTHAALAYAH, 2015)
Music is the soul of Indian culture, music has been an integral part of Indian culture since its inception, in the present times, in busy, stressful and competitive social conditions, music is the only art that can hurt human's mind and soul for some time. Provides true happiness for संगीत कला भारतीय संस्कृति की आत्मा है, भारतीय संस्कृति के उद्भव काल से ही संगीत इसका अभिन्न अंग रहा है, वर्तमान समय में व्यस्त, तनावपूर्ण एवं प्रतियोगी सामाजिक परिस्थितियों में संगीत ही एक ऐसी कला है, जो मनुष्य के आहत मन एवं आत्मा को कुछ समय के लिए ही सही सुख प्रदान करती है ।